Non-invasive optical method for evaluating the oxygen status in breast neoplasms - A. V. Maslennikova; G. Yu. Golubyatnikov; A. G. Orlova; V. I. Plekhanov; A. A. Artifeksova; N. M. Shakhova; V. A. Kamensky; I. V. Turchin (ABV-press, 2014)
The paper presents the results from a study of the breast oxygen status by diffuse optical tomography (DOT). Detection of breast tissue at wavelengths of 684, 794, and 850 nm could provide information on the distribution of basic tissue chromophores: oxygenized and deoxygenized hemoglobin. Normal breast tissue was characterized by the even distribution of these compounds and stabilization of their level. In breast cancer, the distribution of oxy- and deoxyhemoglobin was noted for uneven distribution and blood oxygen saturation was lower in the projection of a tumor nodule. The blood oxygen saturation data obtained by DOT demonstrate physiological differ- ences between normal and tumor tissues in different tumor areas.